Risk Factors of Subependymal Hemorrhage-Intraventricular Haemorrhage in Preterm Infants - Gulbin Shahid ,Mahmood Jamal , Yasir Bin Nisar (Journal of Rawalpindi Medical College, 2017)
To determine the frequency and peak time of occurrence of subependymal hemorrhageintraventricular hemorrhage (SEH-IVH) in preterm infants and to identify the predisposing risk factors. Methods: In this descriptive study consecutive live born babies (n=135), between the gestational ages of 28-34 weeks, were enrolled. Information regarding weight, gestational age, mode of delivery and presence of risk factors were recorded. Each newborn underwent cranial ultrasound on designated days and was followed up till the fourth week of life unless expired. Results: The frequency of SEH-IVH was found to be 20.8%. The most vulnerable group in terms of gestational age and weight were infants < 32 wks and weighing < 1.5 kg respectively. The peak age of occurrence of SEH-IVH was first three days of life. Risk factors found to be associated with SEH-IVH were RDS with ventilation, exchange transfusion and thrombocytopenia. Conclusion: The incidence of SEH-IVH in infants between 28-34 wks gestation is significantly high. The crucial period is the first three days of life and respiratory distress syndrome (RDS) with ventilation, exchange transfusion and thrombocytopenia carry the highest risk of hemorrhage. There is a need to emphasize on the prevention of prematurity and optimum perinatal management to minimize the risk of hemorrhage.